Service Marketing Strategies for the New Milennium in Banking Sector - Saravan, S. (Indian Journal of Marketing, 2004)
A 'service', in common terms, is defined as an act or performance offered by one party to another free of cost, or for consideration. 'Marketing' is a function by which a marketer plans, promotes and delivers goods and services to the clients and customers. Services are many fold in nature, ranging from personal services like hair cutting, tailoring, auto repairing, medical services, legal consultancy etc to public utility services like roadways, tourism, postal, health care, professional care, insurance, Financial service viz banking and many more. Likewise, in the field of 'marketing' also, we have divisions like 'marketing of goods' and 'marketing of services'. 'Goods' are physical objects like food, books, cloths, domestic or industrial items that can be created/stored in a particular place or transferred from one place to another. They are tangible in nature. But 'services' are non - physical in nature and hence, have no transferability. They cannot also be stored for the future. If a service is not used, today, it is lost once for all.